Overview of Atmanirbhar Bharat Rojgar Yojna (ABRY): How to Avail It's Benefits and It's Impact on New Employment - Kumar, Manish (Journal of Commerce and Trade, 2021)
The Union Cabinet has given its approval for Atmanirbhar Bharat Rojgar Yojana (ABRY) to boost employment in formal sector and incentives creation of new employment opportunities during the Covid recovery phase under Atmanirbhar Bharat Package 3.0. Government will pay both 12% employees' contribution and 12% employers' contribution i.e. 24% of wages towards EPF in respect of new employees in establishments employing up to 1000 employees for two years.3.Government will pay only employees' share of EPF contribution i.e. 12% of wages in respect of new employees in establishments employing more than 1000 employee for two years. To support the Government and give wings to their dream, we, as an Aatmanirbhar Sena, do our best to avail all possible assistance to it. We shall give our best to convert the time of crisis into opportunity by aiding the youths and people in pain. We shall ensure our full-time assistance for those who wish to have their benefits and live their dreams again. We shall strive to provide round-the-clock assistance who wants to join the league of availing the services of the Scheme. Atmanirbhar Bharat Rozgar Yojana is a proper mechanism to boost the employment rate and development in India. Atmanirbhar Bharat Rozgar Yojana is like a rising sun that has come up, spreading its light mitigating the darkness from the lives of our Nation's people. It is no less than a second life for people in distress. Classification-JEL: F66, J21